2018
DOI: 10.1021/acs.inorgchem.8b00975
|View full text |Cite
|
Sign up to set email alerts
|

A Key Factor Dominating the Competition between Photolysis and Photoracemization of [Ru(bipy)3]2+ and [Ru(phen)3]2+ Complexes

Abstract: Photolysis and photoracemization are two important photochemical phenomena of the prototype complexes [Ru(bipy)] and [Ru(phen)] (bipy = 2,2'-bipyridine, phen = 1,10-phenanthroline), but little is known about their relations. To solve this issue, the photoinduced chiral inversion Δ⇌Λ of the complexes was analyzed theoretically. The results indicated that the photoracemization reaction proceeds on the lowest triplet potential energy surface in three steps CT↔MC, MC↔MC, and MC↔CT (CT = charge transfer state; MC =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Two differently substituted bpy ligands can form diastereomers even for mononuclear complexes [Ru(bpy)(bpy R )(bpy R’ )] 2+ . Finally, bidentate ligands are comparably photolabile enabling photoisomerization of the complex or photosubstitution of the ligands . Replacing bpy by the tridentate ligand 2,2’:6’2’’‐terpyridine (tpy) yields achiral, comparably photostable [Ru(tpy) 2 ] 2+ complexes (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Two differently substituted bpy ligands can form diastereomers even for mononuclear complexes [Ru(bpy)(bpy R )(bpy R’ )] 2+ . Finally, bidentate ligands are comparably photolabile enabling photoisomerization of the complex or photosubstitution of the ligands . Replacing bpy by the tridentate ligand 2,2’:6’2’’‐terpyridine (tpy) yields achiral, comparably photostable [Ru(tpy) 2 ] 2+ complexes (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies have provided highly illuminating results in this regard, which have shed light on the nature of these important excited states. Numerous reports have detailed the pivotal role of 3 MC states in mediating photochromic and photoracemization , reactions of metal complexes and photochemical ligand substitution reactivity. These studies reveal that metal complexes can access a number of 3 MC states of differing geometric and electronic character . Further, investigations have suggested that structural modification of complexes can modulate the relative accessibility of different 3 MC states, states which may have preferential roles in either promoting ground-state recovery or ligand substitution, thus modulating the photochemical ligand substitution efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies have provided highly illuminating results in this regard, which have shed light on the nature of these important excited states. Numerous reports have detailed the pivotal role of 3 MC states in mediating photochromic 40 42 and photoracemization 43 , 44 reactions of metal complexes and photochemical ligand substitution reactivity. 45 50 These studies reveal that metal complexes can access a number of 3 MC states of differing geometric and electronic character.…”
Section: Introductionmentioning
confidence: 99%